REGULATORY AND LEGAL ASPECTS OF DIGITAL AUTOMOTIVE PLATFORMS IN THE UNITED STATES: BARRIERS AND OPPORTUNITIES FOR SCALING (American Journal of Technology and Applied Sciences, 2026)
This article examines the scope and role of various types of digital services and platforms in the U.S. automotive sector, as well as the factors and barriers that may influence the successful scaling and development of such projects. The introductory section traces the historical development of the automotive industry and new transportation technologies. The main section describes various modern types of digital platforms, including those enabled by the digitization of telematics and vehicle data, services for autonomous driving, car-sharing, and the automation of transportation systems within the framework of “smart” cities and regions. The analysis examines relevant federal and state laws and policies, positions on liability issues related to the use of AI in vehicles, as well as intellectual property and cybersecurity issues. The main barriers affecting the scalability of services and platforms include: insufficient legal regulation in the specific area of interoperability and standards, high implementation risks and costs, and a lack of trust among consumers and investors. At the same time, a number of case studies are presented that illustrate the potential for the development and scaling of modern digital services and platforms through integration with cutting-edge technologies, partnerships with the government and private sector, the development of “smart” infrastructure, and flexible regulation in the form of soft law and smart law combined with traditional legislation and minimal government intervention. In conclusion, the authors conclude that successful business models for digital technologies in the automotive industry, including in the field of robotaxis, are generally based on a comprehensive approach utilizing the latest regulatory provisions and standards, as well as on appeal and trust among consumers and investors.